The English-speaking, Hungarian, Latvian, Lithuanian, Romanian, Russian, Slovak, and Spanish adaptations of Makarowski`s Stimulating and Instrumental Risk Questionnaire for martial arts athletes - Makarowski, R.; Piotrowski, A.; Predoiu, R.; Görner, K.; Predoiu, A.; Mitrache, G.; Malinauskas, R.; Vicente-Salar, N.; Vazne, Z.; Cherepov, E.; Miklósi, M.; Kovács, K.; et al. (Archives of Budo, 2021)
Background and Study Aim: The competition is an unique event which supposes pressure, social and financial stake, in these conditions increasing the athletes` probability of getting injured. And this probability is higher in the case of new and inexperienced athletes, in which case (mainly), the win-at-all-costs philosophy may lead to less calculated risks. The goal of the current study is recommendation to researchers, coaches of various martial arts (combat sports) disciplines, physical education teachers, and psychologists with a measure of stimulating and instrumental risk. Adapting the S&IRQ will allow for assessing athletes in terms of sports risk